Neonatal Polycystic Kidney Disease in a One-Day-Old Baby: A Case Report - Mchaile D; Mrindoko P; Mselle M; Meleki E; Kimambo E; Likiliwike A; Lodhia J (Dove Medical Press, 2020)
Deborah Mchaile,1,2 Philip Mrindoko,2 Matei Mselle,2 Elton Meleki,2 Elise Kimambo,2 Arnold Likiliwike,2 Jay Lodhia3 1Department of Paediatrics and Child Health, Kilimanjaro Christian Medical University College, Moshi, Tanzania; 2Department of Paediatrics and Child Health, Kilimanjaro Christian Medical Centre, Moshi, Tanzania; 3Department of General Surgery, Kilimanjaro Christian Medical Centre, Moshi, TanzaniaCorrespondence: Deborah Mchaile Email deborahsia@hotmail.co.ukBackground: Polycystic kidney disease in neonates is a rare genetic disease which can be either autosomal dominant or autosomal recessive with each presenting at a certain period in life. They can both be diagnosed before or after birth using fetal ultrasound. This is a case of a five-hour-old baby with suspected polycystic kidney disease in a tertiary hospital in northern Tanzania.Case Presentation: We present a case of a five-hour-old female baby referred to us with a complaint of non-progressive abdominal distension since birth. The birth weight was 2.4 kilograms with a good APGAR score. Clinically, the baby had palpable kidneys bilaterally, widened anterior fontanelle communicating with the posterior as well as rocker bottom feet. Her abdominal ultrasound showed bilaterally enlarged echogenic kidneys with loss of cortico-medullary differentiation and multiple tiny cystic spaces. An echocardiogram showed patent ductus arteriosus and moderate tricuspid regurgitation with mild pulmonary regurgitation. The patient was started on medication but unfortunately on day two post admission the baby succumbed.Conclusion: Neonatal polycystic kidney disease is associated with high morbidity and mortality rates. It may not be as rare as previously reported. Minimal to no awareness exists on the condition or its effects in our setup due to underdiagnosis and neither availability of neonatal screening nor availability of genetic analysis. It is likely underdiagnosed due to a lack of skills in fetal ultrasounds and no neonatal ICU to care for these babies. Increased awareness will increase the index of suspicion. This is the first case report in our setup highlighting this condition.Keywords: newborn screening, polycystic kidney disease, ultrasound